Evolution of land plants: insights from molecular studies on basal lineages. Issue 1 (2nd January 2017) - Ishizaki, Kimitsune
Abstract: The invasion of the land by plants, or terrestrialization, was one of the most critical events in the history of the Earth. The evolution of land plants included significant transformations in body plans: the emergence of a multicellular diploid sporophyte, transition from gametophyte-dominant to sporophyte-dominant life histories, and development of many specialized tissues and organs, such as stomata, vascular tissues, roots, leaves, seeds, and flowers. Recent advances in molecular genetics in two model basal plants, bryophytes Physcomitrella patens and Marchantia polymorpha, have begun to provide answers to several key questions regarding land plant evolution. This paper discusses the evolution of the genes and regulatory mechanisms that helped drive such significant morphological innovations among land-based plants. Graphical abstract: : Evolution of land plants and alternation of generation.